FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PROFESI AKUNTAN TERHADAP PRAKTEK EARNINGS MANAGEMENT - Ishar Baharuddin; Heru Satyanugraha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
This study examines the ethics of earnings management practice ofaccount- ing practioners, faculty, and students in Indonesia. Possible detenninants of the ethics, the personal moral philosophies (i.e. idealism and relativism), and the perceived role of ethics and social responsibility were empirically tested. Data for the study were collected from Trisakti university's students, faculty of universities in Jakarta, and auditors of accounting fi4ms in Jakarta. A multiple regression analysis was used to test the hypotheses. The findings indicate a positive relationship between idealism and social responsibility focus on long-term gains, and the ethical perception of earnings management.Keywords: Accounting ethics, earnings management, ethics determinants, per-sonal moral philosophies, social responsibility